Association of glycerolipid metabolism with gut microbiota disturbances in a hamster model of high-fat diet-induced hyperlipidemia - Han, Lijie; Hu, Chaowei; Du, Zhiyong; Yu, Huahui; Du, Yunhui; Li, Linyi; Li, Fan; Wang, Yu; Gao, Xiaoqian; Sun, Xuechun; Zhang, Zihan (Frontiers in Cellular and Infection Microbiology, 2024)
BackgroundHigh-fat diet (HFD)-induced hyperlipidemia, which is associated with gut microbiota disturbances, remains a major public health challenge. Glycerolipid metabolism is responsible for lipid synthesis and is thus involved in the development of hyperlipidemia. However, possible association between the HFD-modulated gut microbiome and the glycerolipid metabolism pathway remains unclear.MethodsHamsters were fed a HFD for 4 weeks to establish a hyperlipidemia model. Fecal, plasma and liver samples collected from hamsters fed a HFD or a normal chow diet (NCD) were used for integrative metagenomic and untargeted metabolomic analyses to explore changes in the composition and functions of the gut microbiota, and relevant metabolites. Spearman rank correlation analysis was used to explore correlations between gut microbes and circulating glycerolipid metabolites, gut microbes and lipids, and circulating glycerolipid metabolites and lipids.ResultsThe gut microbial composition of HFD hamsters showed significant alterations at the phylum, genus, and species levels that were skewed toward metabolic disorders compared with that of NCD hamsters. Functional characterization by KEGG analysis identified enrichment of the glycerolipid metabolism pathway in the gut microbiome of HFD hamsters. Plasma and liver metabolomics further indicated the upregulation and enrichment of glycerolipid metabolites in HFD hamsters. The Faecalibaculum, Allobaculum, and Eubacterium genera were positively correlated with plasma glycerolipid metabolites and lipid indices.ConclusionThe findings of this study suggest an association between glycerolipid metabolism and the HFD-modulated gut microbiome that is involved in the development of hyperlipidemia.